Injury prevention for throwing athletes Part I: Baseball bat training to enhance medial elbow dynamic stability - Crotin, R. L.; Ramsey, D. K. (Strength and Conditioning Journal, 2012)
Baseball pitchers' elbows are exposed to medial traction, lateral compression, and posteriomedial shear forces. Factors attributed to injury severity include overuse, poor throwing mechanics, orthopedic maturity, and reduced muscle strength. The anterior band of the ulnar collateral ligament (ucl) is the main structure to withstand tensile stress in pitchers. When overwhelmed, ligament reconstruction is required through a procedure known as tommy john surgery. Part i of the 2 part series presents a baseball bat training strategy to improve muscular support for the pitching elbow in protecting the ucl.